Analisis Faktor-Faktor Yang Berpengaruh Terhadap Penerimaan Aplikasi Puskesmas Tanpa Antrian (PUSTAKA) di Puskesmas Rowosari - Lutfiyah Rizqulloh; Muhammad Iqbal; Adelia Puspitasari (Indonesian of Health Information Management Journal (INOHIM), 2022)
AbstractProblems that occur in Puskesmas services are often related to waiting times to provide services to patients who are still long. To deal with this, the Semarang City Health Office made a policy for Puskesmas Tanpa Antrian Kota Semarang (PUSTAKA). One of the PUSTAKA implementations is at the Rowosari Health Center, in recent years it has decreased in 2020 and has increased in 2022. The purpose of the study was to determine the influencing factors based on the Technology Acceptance Mode (TAM) model on the acceptance of the PUSTAKA application to Rowosari Health Center visitors. Quantitative research using a cross sectional design. The sample came from 145 visitors to the Rowosari Health Center, processing data with Univariate, Bivariate and Multivariate analysis with multiple logistic regression tests. The results show the relationship between perceived ease of use p = 0.000 with OR = 7.056, perceived usefulness p = 0.000 with OR = 5.749, Attitude Toward Using p = 0.002 with OR = 3.630, Behavioral Intention to Use p = 0.023 with OR = 2,429 towards the use of the PUSTAKA application for visitors to the Rowosari Health Center. Acceptance of literature at the Rowosari Health Center has a significant relationship with perceptions of convenience, Perceived Usefulness, Perceived Ease of Use, Behavioral Intention to Use and Attitude Toward Using in the Technology Acceptance Mode (TAM) Model. The usefulness variable is the most dominant variable on the use of the LIBRARY application with an OR value of 5.239.Keyword: Rowosari Health Center, PUSTAKA, Technology Acceptance Model AbstrakProblem yang terjadi pada pelayanan Puskesmas sering berhubungan di waktu tunggu untuk memberikan pelayanan kepada pasien yang masih lama. Menanggulangi hal tersebut Dinas Kesehatan Kota Semarang membuat kebijakan Program Puskesmas Tanpa Antrian Kota Semarang (PUSTAKA). Salah satu Pelaksanaan PUSTAKA yaitu di Puskesmas Rowosari, dalam beberapa tahun terakhir mengalami penurunan ditahun 2020 dan mengalami kenaikan ditahun 2022. Tujuan penelitian untuk mengetahui faktor yang mempengaruhi berdasarkan model Technology Acceptance Mode (TAM) terhadap penerimaan aplikasi PUSTAKA  pada Pengunjung Puskesmas Rowosari. Penelitian dengan Kuantitatif menggunakan desain Cross Sectional. Sampel berasal dari 145 Penunjung Puskesmas Rowosari, pengolahan data dengan analisis Univariat, Bivariat dan Multivariat dengan uji regresi logistik berganda Hasil menunjukan hubungan antara persepsi kemudahan p= 0,000 dengan OR= 7,056, persepsi kebermanfaatan p= 0,000 dengan OR= 5,749, sikap pengguna p= 0,002 dengan OR= 3,630, persepsi minat p= 0,023 dengan OR= 2,429) terhadap penggunaan aplikasi PUSTAKA pada pengunjung Puskesmas Rowosari. Penerimaan PUSTAKA di Puskesmas Rowosari memiliki hubungan yang signifikansi terhadap persepsi kemudahan, persepsi kemanfaatan, sikap pengguna dan persepsi minat dalam Technology Acceptance Model (TAM). Variabel kebermanfaatan menjadi variabel yang paling dominan terhadap penggunaan aplikasi PUSTAKA dengan nilai OR = 5,239.Kata Kunci: Puskemas Rowosari, PUSTAKA, Technology Acceptance Model